Development of Responsive Feeding Knowledge, Attitude, and Practices Questionnaire (RF-KAP Q) for Toddlers in Indonesia - Rachma Purwanti; Ani Margawati; Ayu Rahadiyanti; Dewi Marfu'ah Kurniawati (Media Gizi Indonesia, 2026)
There is a need for instruments with good validity and reliability to assess three domains of responsive feeding practices in early childhood in Indonesia. This study aims to analyze the validity and reliability of the responsive feeding knowledge, attitude, and practice instrument, which was developed for children under three years old. A cross-sectional design examined the validity among diverse toddler parents. The variables studied include knowledge, attitude, and practice of responsive feeding. The questionnaire is structured as doing or not doing practice, attitudes in true or false statements, and knowledge in multiple-choice questions. The construct validity of the Responsive Feeding Knowledge, Attitude, and Practice questionnaire (RF-KAP Q) was evaluated by determining the Pearson correlation coefficient values for each item with the overall score. Additionally, a reliability test was performed to assess the internal consistency of the questionnaire. Cronbach's alpha coefficient measured internal consistency. The 20 items of responsive feeding knowledge questions were categorized as valid; two items were categorized as constant (K6 and K7), and one other was classified as invalid (K14). A total of 25 attitude statement items were considered valid. All practice indicators consisting of 12 statement items were categorized as valid (p-value<0.05). The Cronbach's alpha of the responsive feeding knowledge, attitude, and practices questionnaire was 0.677, 0.699, and 0.778, indicating reliability. The RF-KAP Q has been tested as valid and reliable in measuring three domains of responsive feeding based on evidence-based recommendations in Indonesia. However, development is still needed to improve its validity.